Actors, strategic fields, and game rules: Examining governance at the U.S.-Mexico border in the twenty-first century - Payan Alvarado, Luis Antonio (University of Arizona Press, 2020)
The northern and southern borders and borderlands of the United States should have much in common; instead they offer mirror articulations of the complex relationships and engagements between the United States, Mexico, and Canada. In North American Borders in Comparative Perspectiveleading experts provide a contemporary analysis of how globalization and security imperatives have redefined the shared border regions of these three nations.